Benefits and Risks of Digital Business Transformation: The Example of Eastern Europe Countries - Петруненко, Ярослав Вікторович; Петруненко, Я. В.; Петруненко, Ярослав Викторович; Petrunenko, Yaroslav V.; Petrunenko, Iaroslav V.; Золковер, Андрій Олександрович; Золковер, А. О.; Золковер, Андрей Александрович; Zolkover, Andrii O.; Ястремська, Олеся Олександрівна; Ястремська, О. О.; Ястремская, Олеся Александровна; et al. (Webster University, 2022)
The purpose of this research was to conceptually substantiate an effective business digitalization strategy in Eastern Europe (EE), taking into account the identification of destructive and complementary factors of digital transformation (DT). The survey, completed by top managers of companies from different sectors of the EE countries' economy, helped form a system of indicators for assessing the level of DT by country. The systematization of the DT factors made it possible to differentiate them by the nature of influence, advantages, and threats of the DH (digital humanities) for the EE countries. The results indicated a low and medium level of DT in the countries studied because of the lack of a digitalization strategy. A matrix of business digitalization management strategies has been formed for Eastern European countries, considering the efficiency level, digitalization threats, and the priority in their management. It will help mitigate the threats of DT and reduce the digital divide with countries with a high level of DT.

Метою цього дослідження було концептуальне обґрунтування ефективної стратегії цифровізації бізнесу у Східній Європі (СЄ) з урахуванням виявлення деструктивних та взаємодоповнюючих факторів цифрової трансформації (ЦТ). Опитування, проведене топ-менеджерами компаній з різних секторів економіки країн СЄ, допомогло сформувати систему показників для оцінки рівня ЦТ за країнами. Систематизація факторів ЦT дозволила диференціювати їх за характером впливу, перевагами та загрозами ЦТ (цифрових гуманітарних наук) для країн СЄ. Результати вказували на низький та середній рівень ЦT у досліджуваних країнах через відсутність стратегії цифровізації. Для країн Східної Європи сформовано матрицю стратегій управління цифровизацією бізнесу з урахуванням рівня ефективності, загроз цифровізації та пріоритетності в управлінні ними. Це допоможе пом’якшити загрози ЦT та зменшити цифровий розрив у країнах із високим рівнем ЦT.
Zolkover A. Benefits and Risks of Digital Business Transformation: The Example of Eastern Europe Countries / A. Zolkover, I. Petrunenko, O. Iastremska, O. Stashkevych, M. Mehdizade // Journal of Eastern European and Central Asian Research. – Vol. 9. – № 2. - Webster University, 2022. – Р. 344-356.
Keywords: digital transformation; business; Eastern Europe; digital technology; strategy; digital economy; цифрова трансформація; бізнес; Східна Європа; цифрові технології; стратегія; цифрова економіка; Research Subject Categories::SOCIAL SCIENCES::Business and economics